A professor like me the influence of instructor gender on college achievement - Hoffmann, Florian; Oreopoulos, Philip (National Bureau of Economic Research, 2007)
Many wonder whether teacher gender plays an important role in higher education by influencing student achievement and subject interest. The data used in this paper helps identify average effects from male and female college students assigned to male or female teachers. In contrast to previous work at the primary and secondary school level, our focus on large first-year undergraduate classes isolates gender interaction effects due to students reacting to instructors rather than instructors reacting to students. In addition, by focusing on college, we examine the extent to which gender interactions may exist at later ages. We find that assignment to a same-sex instructor boosts relative grade performance and the likelihood of completing a course, but the magnitudes of these effects are small. A same-sex instructor increases average grade performance by at most 5 percent of its standard deviation and decreases the likelihood of dropping a course by 1.2 percentage points. The effects are similar when conditioning on initial ability (high school achievement), and ethnic background (mother tongue not English), but smaller when conditioning on mathematics and science courses. The effects of same-sex instructors on upper-year course selection are insignificant.
Literaturverz. S. 20 - 21